Резисторный каскад предварительного усиления на биполярном транзисторе - Деарт Ю. Н. (1975)
Экземпляры: КХ (20160516) / Инвентарный номер: 0229291 / Сис.шифр: 621.38 / Авт.знак: Д 25 / ГРНТИ: 47 / ББК: 32